Degree of Phosphorus Saturation and Soil Phosphorus Thresholds in an Ultisol Amended with Triple Superphosphate and Phosphate Rocks. (2011) - Gikonyo, E. W.; Zaharah, A. R.; Hanafi, M. M.; Anuar, A. R.
Abstract : Soil phosphorus (P) release capability could be assessed through the degree of P saturation (DPS). Our main objective was to determine DPS and, hence, P threshold DPS values of an Ultisol treated with triple superphosphate (TSP), Gafsa phosphate rocks (GPR), or Christmas Island phosphate rocks (CIPR), plus or minus manure. P release was determined by the iron oxide—impregnated paper strip (strip P), while DPS was determined from ammonium oxalate—extractable aluminum (Al), iron (Fe), and P. Soils were sampled from a closed incubation study involving soils treated with TSP, GPR, and CIPR at 0–400 mg P kg -1, and a field study where soils were fertilized with the same P sources at 100–300 kg P ha -1 plus or minus manure. The DPS was significantly influenced by P source x P rate, P source x manure (incubated soils), and by P source x P rate x time (field-sampled soils). Incubated soil results indicated that both initial P and total strip P were related to DPS by exponential functions: initial strip P = 1.38exp 0.18DPS, R 2 = 0.82** and total strip P = 8.01exp 0.13DPS, R2 = 0.65**. Initial strip P was linearly related to total P; total P = 2.45, initial P + 8.41, R 2 = 0.85**. The threshold DPS value established was about 22% (incubated soil). Field soils had lower DPS values <12% and strip P was related to initial DPS and average DPS in exponential functions: strip P = 2.6exp 0.44DPS, R 2 = 0.77** and strip P = 1.1DPS 2 — 2.4DPS + 6.2, R 2 = 0.58**, respectively. The threshold values were both at ≈8% and P release was 11–14 mg P kg -1 . Results are evident that DPS can be used to predict P release, but the threshold values are environmentally sensitive; hence, recommendations should be based on field trials.